SYT7 regulates the progression of chronic lymphocytic leukemia through interacting and regulating KNTC1 - Wenjie Zhang; Jinlan Long; Peixia Tang; Kaili Chen; Guangyao Guo; Zezhong Yu; Jie Lin; Liping Liu; Rong Zhan; Zhenshu Xu (BMC, 2023)
Abstract Background Chronic lymphocytic leukemia (CLL) is one of the most frequent occurring types of leukemia. It typically occurs in elderly patients and has a highly variable clinical course. At present, the molecular mechanism driving the pathogenesis and progression of CLL is not fully understood. The protein Synaptotagmin 7 (SYT7) encoded by the SYT7 gene has been found to be closely related to the development of various solid tumors, but its role in CLL is unclear. In this study, we investigated the function and molecular mechanism of SYT7 in CLL. Methods The expression level of SYT7 in CLL was determined by immunohistochemical staining and qPCR. The role of SYT7 in promoting CLL development was verified by in vivo and in vitro experiments. The molecular mechanism of SYT7 in CLL was elucidated by methods such as GeneChip analysis and Co-immunoprecipitation assay. Results Malignant behaviors such as proliferation, migration, and anti-apoptosis of CLL cells were significantly inhibited after SYT7 gene knockdown. In contrast, SYT7 overexpression promoted CLL development in vitro. Consistently, the knockdown of SYT7 also inhibited xenograft tumor growth of CLL cells. Mechanistically, SYT7 promoted CLL development by inhibiting SYVN1-mediated KNTC1 ubiquitination. The KNTC1 knockdown also attenuated the effects of SYT7 overexpression on development of CLL. Conclusions SYT7 regulates the progression of CLL through SYVN1-mediated KNTC1 ubiquitination, which has potential value for molecular targeted therapy of CLL.